Perencanaan Dewatering Pembangunan Gedung Fasilitas Pengembangan Produk Skala Pilot Bio Farma - Dendi Yogaswara; Nurholisah (Institut Teknologi Garut, 2026)
Dewatering is used to lower the groundwater level in order to prevent uplift forces from interfering with construction work. Dewatering is generally used in the construction of high-rise buildings that will usually add a basement floor. The purpose of this study is to determine the need for pumps based on the excavation area, soil type and the amount of water that must be released based on the rain intensity of the Bandung area using the predrainage method. The case study in this research is a 13-story building in the construction project of a pilot-scale product development building (building No. 34) of PT Bio Farma (Persero). The calculation results show that the soil type is inorganic clay with high plasticity and based on the excavation zone of ± 1,516.52 m2 which is divided into three zones, the pump requirements for dewatering work require 3 pumps in each excavation zone with a pump capacity of 150 liters/minute. The amount of water that must be released based on rain intensity data of the Bandung area ± 50 mm obtained the result of 60 m3 / hour.